The Relationship Between Exploitative Show Viewing Habits and Aggressive Behavior in Adolescents - Putera, Feandi; Rahayu, Inong Sri (Asian Journal of Public Health and Nursing, 2024)
Background: Exploitation is a form of crime and violence that can jeopardize a child’s future. Adolescents who frequently watch exploitative content are more likely to exhibit aggressive tendencies and may become desensitized to violence in daily life, leading to both physical and psychological consequences. This study aims to explore the relationship between the habit of watching exploitative shows and aggressive behavior among adolescents. Methods: A cross-sectional study was conducted among 76 adolescents in Aceh, Indonesia. Data on demographics, viewing habits of exploitative shows, and aggressive behavior were collected using a researcher-modified questionnaire. Results: Over half of the respondents were female (57.9%), with the majority categorized as heavy viewers of exploitative shows (69.7%), and aggressive behavior identified in 59.2% of participants. A significant association was found between the habit of watching exploitative shows and aggressive behavior (p-value = 0.002, OR = 5.790). Conclusion: Adolescents who frequently consume exploitative content struggle to regulate their behavior effectively, as the dependency on such shows fosters aggression. Adequate supervision of adolescents is crucial, and it is recommended that social media platforms prioritize broadcasting educational content to promote positive personality development.